Phytoplankton community composition and biomass in the oligotrophic Gulf of Mexico. (8th March 2021) - E Selph, Karen; Swalethorp, Rasmus; R Stukel, Michael; B Kelly, Thomas; N Knapp, Angela; Fleming, Kelsey; Hernandez, Tabitha; R Landry, Michael
Abstract: Biomass and composition of the phytoplankton community were investigated in the deep-water Gulf of Mexico (GoM) at the edges of Loop Current anticyclonic eddies during May 2017 and May 2018. Using flow cytometry, high-performance liquid chromatography pigments and microscopy, we found euphotic zone integrated chlorophyll a of 10 mg m −2 and autotrophic carbon ranging from 463 to 1268 mg m −2, dominated by picoplankton (<2 μm cells). Phytoplankton assemblages were similar to the mean composition at the Bermuda Atlantic Time-series Study site, but differed from the Hawaii Ocean Times-series site. GoM phytoplankton biomass was 2-fold higher at the deep chlorophyll maximum (DCM) relative to the mixed layer (ML). Prochlorococcus and prymnesiophytes were the dominant taxa throughout the euphotic zone; however, other eukaryotic taxa had significant biomass in the DCM. Shallower DCMs were correlated with more prymnesiophytes and prasinophytes (Type 3) and reduced Prochlorococcus . These trends in ML and DCM taxonomic composition likely reflect relative nutrient supply—with ML populations relying on remineralized ammonium as a nitrogen source, and the taxonomically diverse DCM populations using more nitrate. These spatially separated phytoplankton communities represent different pathways for primary production, with a dominance of picoplankton in the ML and more nano- and microplankton at the DCM.